Morphological variation and taxonomic interpretation in the moss genus Bryum in Antarctica - Seppelt, Rodney D.; Kanda, Hiroshi (1986)
P(論文) The potential for morphological variation in Antarctic species of Bryum is evaluated and related to problems associated with taxonomic interpretation based on specimens from the Soya Coast, Mac. Robertson Coast, Vestfold Hills and Knox Coast. B. argenteum HEDW. Has been positively determined for Continental Antarctica from six localities on the Soya Coast and from Ross Island, southern Victoria Land. Specimens from the Vestfold Hills and Knox Coast considered with some reservation as this species are here referred to B. pseudotriquetrum (HEDW.) GAERTN, MEYER et SCHERB. B. pseudotriquetrum is widespread in the Antarctic region and includes many species formerly regarded as distinct taxa. Small specimens and those with physical damage to the upper parts of leaves may confused with B. argenteum. It is concluded that only two species of Bryum, B. argenteum and B. pseudotriquetrum, are represented in the Continental Antarctic flora, confirming H. OCHI'S (Mem. Natl Inst. Polar Res., Spec. Issue, 11, 70, 1979) taxonomic conclusion. departmental bulletin paper